Alternative Design and Construction Method for Clinton CSO Underground Storage Facility - Paul Beljan; Meeok Kim; Gordon Chen (Deep Foundations Institute, 2015)
"Clinton combined sewer overflow storage (CSO) facility project developed by the Department of Water Environment Protection of Onondaga County, New York, is to improve sewer facilities and infrastructure in Syracuse, New York. The below grade facility will provide a storage of untreated stormwater during highflow periods to be treated later, thus reducing CSO discharges to Onondaga Creek.The CSO system consists of three parallel storage tunnels and two end chambers (west and east chambers) as main underground structure. The storage tunnels are about 850 ft. long, 55 ft. wide, 24 ft tall and located 20 ft deep below grade. The chambers, include above access and operation structure, are about 40 to 55 ft. deep and approximately 60 to 100 ft. wide.Kiewit Infrastructure and Weidlinger Associates Inc. developed an alternative approach for the tunnels to meet the facility completion schedule, strict design guide lines and quality control as an environmental and water tight concrete structure for the project. The original design anticipated use of a TBM machine to bore three parallel tunnels between two previously constructed chambers.The alternative design used a three barrel culvert cast-in-place structure in a cut and cover excavation supported by a soil bentonite wall. The SOE along the jet grouted bottom seal provided a ground water cut off as well.The SOE system is specially designed to enhance the quality of culvert CIP structure construction by providing enough space for a full height construction. Also it further reduces the construction time by having the less squarefootage of jet grout installation. The design of tunnel systems is accomplished effectively through the utilization of soil structure interaction using a finite element methodIntroductionTo avoid construction of an additional treatment plant to handle increases in combined sewage flows, the Department of Water Environment Protection of Onondaga opted to construct the Clinton combined sewer overflow storage (CSO) facility.The Clinton CSO facility provides an environmental friendly mitigation method for combined sewer overflows on Onondaga lake which is located in northwest of Syracuse."